(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Smorodskyi V. I. Organizational and pedagogical conditions of performance skills formation of music schools pupils on the basis of genre approach. In the article methodological meaning of the term «Pedagogical conditions» was analysed. Pedagogical conditions of performance skills formation of music schools pupils on the basis of genre approach were difined. They are the formation of motivational direction of teaching process for mastering performance skills on the basis of genre approach; choice of content, forms, methods and means of performance skills formation on the basis of genre approach; building of dialogic communication between a teacher and a pupil as bases of performance skills formation on the basis of genre approach.